2010
DOI: 10.3109/15622970903559925
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy: A review of knowledge, experience and attitudes of patients concerning the treatment

Abstract: Overall, the weight of the evidence supports the notion that patients undergoing ECT are well-disposed towards it. However, much needs to be done to improve the practice of ECT and to enhance patients' satisfaction with the experience of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 59 publications
5
51
0
6
Order By: Relevance
“…After beneficial effects of ECT and improvement in post-ECT psychopathology, subjects will have favorable attitude and increased satisfaction toward ECT. Positive experience of treatment will have enduring impact on subjects' perceptions, ECT should be used only when indicated 5 . Information leaflets and audio-visual aids play additional benefit when given information about the procedure; especially visual demonstrations are very valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After beneficial effects of ECT and improvement in post-ECT psychopathology, subjects will have favorable attitude and increased satisfaction toward ECT. Positive experience of treatment will have enduring impact on subjects' perceptions, ECT should be used only when indicated 5 . Information leaflets and audio-visual aids play additional benefit when given information about the procedure; especially visual demonstrations are very valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Ironically there is widespread negative view of ECT in common people and other medical fraternities. This are various reasons-irrational fear of electricity, primitive practices in the past (but new ECT machine has been in use for last 30 years) 5, negative media representations-in mass media and in popular films 6, 7. ECT has falsely been epitomized as a symbol of repressive, authorities and inhuman behavior toward innocent and exploited 8 . Researches in ECT have focused on various aspects-efficacy, side effects, mechanism of action.…”
Section: Introductionmentioning
confidence: 99%
“…While most literature has focused on negative ECT experiences, some research does document positive patient accounts (Chakrabarti et al, 2010;Rajkumar, Saravanan, & Jacob, 2006), and some heterogeneity (Rose, Fleischmann, Wykes, Leese, & Bindman, 2003). We could not find any research that specifically attempted to interpret and connect these disparate accounts.…”
Section: Introductionmentioning
confidence: 46%
“…However, the literature also indicates that patient experiences are highly variable, with strongly positive assessments also prevalent, e.g. relating to satisfaction with the adequacy of information provision, safety of the treatment, and willingness to receive ECT again (Chakrabarti, Grover, & Rajagopal, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst many patients have a favourable experience of ECT, a review showed that a sizeable proportion report poor information about the treatment itself and possible side effects (Chakrabarti et al, 2010). Good practice in ECT requires close attention to safety and monitoring (Scott, 2004).…”
Section: How Should Treatment Be Delivered?mentioning
confidence: 99%